2021
DOI: 10.3389/fphys.2021.710968
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the Muscarinic M3 Receptor by Myocardin-Related Transcription Factors

Abstract: Myocardin-related transcription factors (MRTFs: myocardin/MYOCD, MRTF-A/MRTFA, and MRTF-B/MRTFB) are co-factors of serum response factor (SRF) that activate the smooth muscle cell (SMC) gene program and that play roles in cardiovascular development and mechanobiology. Gain and loss of function experiments have defined the SMC gene program under control of MRTFs, yet full understanding of their impact is lacking. In the present study, we tested the hypothesis that the muscarinic M3 receptor (CHRM3) is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Upon first reflection, this contradiction makes little sense, but it is possible that the different MRTFs are expressed in entirely different cell types with different roles in vascular inflammation. Indeed, in parallel work ( Liu et al, 2021 ) we find that MYOCD is enriched in SMCs as expected, and that MRTF-B is enriched in endothelial cells, while MRTF-A primarily resides in fibroblasts. Additional explanations for the discrepant effects of MRTF-A and MYOCD in atherosclerosis include coactivator-specific effects.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Upon first reflection, this contradiction makes little sense, but it is possible that the different MRTFs are expressed in entirely different cell types with different roles in vascular inflammation. Indeed, in parallel work ( Liu et al, 2021 ) we find that MYOCD is enriched in SMCs as expected, and that MRTF-B is enriched in endothelial cells, while MRTF-A primarily resides in fibroblasts. Additional explanations for the discrepant effects of MRTF-A and MYOCD in atherosclerosis include coactivator-specific effects.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we show that overexpression of MRTFs downregulate several pro-inflammatory transcripts and proteins relevant for vascular pathophysiology and development of vascular disease. However, the RNA-seq experiment providing impetus for the present work ( Liu et al, 2021 ) revealed additional pro-inflammatory genes, such as SGPP2 (sphingosine 1-phosphate phosphatase 2), IL32 (interleukin 32), and TSLP (thymic stromal lymphopoietin), as being repressed. Notably, downregulation of SGPP2 gene activity and sphingosine 1-phosphate phosphatase 2 protein levels reduces TNFα-induced IL1B and CXCL8 production in endothelial cells, and moreover, knockdown of NF-κB/RelA shows that SGPP2 is an NF-κB-regulated gene ( Mechtcheriakova et al, 2007 ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations